The cubic S-curve relationship between board independence and intellectual capital efficiency: does firm size matter? - Kweh, Qian Long; Lu, Wen-Min; Ting, Irene Wei Kiong; Hanh, Le Thi My (Emerald Publishing Limited, 2021)
Purpose – First, this study assesses the efficiency of linking intellectual capital (IC) components to firm performance. Second, this study examines (i) the cubic S-curve relationship between board independence and IC efficiency and (ii) how firm size moderates the cubic S-curve relationship. Design/methodology/approach – This study employs a stochastic nonparametric envelopment of data (StoNED) framework to estimate IC efficiency, which is derived from the estimation process of transforming structural, relational, and human capitals into accounting- and market-based performance indicators. This study performs regression analyses on 1,104 firm-year observations of Taiwanese semiconductor firms over the period of 2011–2018. Findings – StoNED results suggest that sample firms’ IC efficiency can be relatively improved by approximately 80%. Regression results indicate that a cubic S-curve relationship between board independence and IC efficiency is found, and firm size moderates the effects. Practical implications – Overall, this study highlights the importance of considering the nonlinear effect of board independence on IC efficiency from the perspective of agency theory, and the moderating firm size, which may suggest availability of resources from the perspective of resource-based view of the firm. Originality/value – This study contributes to the literature through the innovative application of an efficiency-based tool for evaluating IC management. The cubic S-curve relationship between board independence and IC efficiency also points to the policy concerning the appropriate number of independent directors on board.